Preparation, characterization and stability evaluation of astaxanthin nanodispersions - Kouchehbagh, Navideh Anarjan (2012)
Incorporating functional lipid nutraceuticals, such as carotenoids, which suffer from poor water solubility and low bioavailability, into nano-sized delivery systems, such as nanodispersions, can strongly improve the lipid nutraceuticals’ solubility, stability, and bioavailability. In this study, stable astaxanthin nanodispersions were prepared and characterised. Response-surface methodology was employed to investigate the effects of applied pressure (20-90 MPa), the number of cycles (0-4) in the homogeniser, and the evaporation temperature (16-66ºC) on the mean particle size, polydispersity index (PDI) and astaxanthin concentration of polysorbate 20 (PS20)- and sodium caseinate(SC)- stabilised astaxanthin nanodispersion systems. On the basis of this multipleoptimisation procedure, the optimum processing conditions were predicted to be 50 MPa, 2 cycles, and 47C for a PS20-stabilised nanodispersion system and 30 MPa, 3 cycles, and 25C for a SC-stabilised nanodispersion system. To evaluate the formulation parameters, PS20 and gum Arabic (GA) were selected through screening evaluations, and SC was selected based on the literature. A simplex centroid mixture design was used to develop a three-component stabilising system to produce nanodispersions with minimal particle size, PDI, and astaxanthin loss and maximal physical and chemical stabilities. The multiple-response optimisation results predicted that a stabiliser system composed of 29% w/w PS20,6% w/w GA and 65% w/w SC would produce astaxanthin nanodispersions with the most desirable physicochemical and stability characteristics. Another simplex centroid mixture design was employed to study the effects of the organic phase in the formation and characteristics of astaxanthin nanodispersions. Accordingly, nanodispersions. Subsequently, the astaxanthin concentrations (0.02–0.38% w/w),stabiliser concentrations (0.2–3.8% w/w) and organic phase (dichloromethane) concentrations (2–38% w/w) were optimised using response surface methodology and a response optimiser. Overall, optimum conditions for obtaining stable astaxanthin nanodispersions were obtained by combining 0.08% w/w astaxanthin,2.5% w/w stabiliser and 11.5% w/w organic phase. Such optimally formulatedastaxanthin nanodispersions also showed the most desirable characteristics in terms of flow behaviour, cellular uptake, colour, antioxidant activity and microstructure compared with nonoptimised astaxanthin nanodispersions. Stability studies were performed on these optimally produced astaxanthin nanodispersions while varying the heat treatments, pH and concentrations of ions,and these studies confirmed that these astaxanthin nanodispersions were more stable compared with nonoptimised nanodispersions. In addition, although the astaxanthin contents of our prepared nanodispersions were decreased significantly (p < 0.05) during 8 weeks of storage at different temperatures, luminances and atmospheres,the optimally formulated nanodispersions showed less rapid astaxanthin loss and higher chemical stability compared with other nanodispersions.As a result of these optimisation methods, the high chemical stability of astaxanthin nanodispersions in real food systems (orange juice and skimmed milk) has proven their suitability as functional ingredients in a wide range of food, feed (via the aquaculture industry), pharmaceutical, cosmetic and personal-care product formulations.